Analisis Sistem Informasi Penjualan Tanaman Obat Berbasis Web Dengan Metode Pieces Framework - Rachman Komarudin - STMIK Nusa Mandiri Jakarta (Bianglala Informatika, 2017)
Abstract – Analysis of web based medicinal sales information systems is needed to identify the shortcomings and weaknesses of the system. The analytical method used in the process of medicinal sales information system analysis using PIECES analysis method. Based on the calculation results obtained that for the Performance domain with the average value of satisfaction is in the range 3.7 with the category "GOOD", Information and data with the average value of satisfaction is in the range 3.7 with the category "GOOD", Ecomoics with the average value of satisfaction Is in the range of 3.69 with the category of "GOOD", Control and security with the average value of satisfaction is in the range of 3.66 with the category "GOOD", Efficiency with the average value of satisfaction is in the range of 3.52 with the category "GOOD" and service with a flat The satisfaction is in the 3.52 range with the category "GOOD". Based on the average value of the satisfaction of the use of medicinal plants sales information system is in the range of 3.65 with the satisfaction category is "GOOD" so that for the use of medicinal plants sales information system feasible and can be used properly.. Intisari –  Analisis sisem informasi penjualan obat berbasis web diperlukan untuk mengidentifikasi kekurangan dan kelemahan yang ada pada sistem. Metode analisis yang digunakan dalam proses analisis sistem informasi penjualan obat menggunakan metode analisis PIECES. Berdasarkan hasil perhitungan didapat bahwa untuk domain Performance dengan nilai rata-rata kepuasan ada pada range 3.7 dengan kategori “BAIK”, Information and data dengan nilai rata-rata kepuasan ada pada range 3.7 dengan kategori “BAIK”, Ecomoics dengan nilai rata-rata kepuasan ada pada range 3.69 dengan kategori “BAIK” , Control and security dengan nilai rata-rata kepuasan ada pada range 3.66 dengan kategori “BAIK” , Efficiency dengan nilai rata-rata kepuasan ada pada range 3.52 dengan kategori “BAIK” dan service dengan nilai rata-rata kepuasan ada pada range 3.52 dengan kategori “BAIK”. Berdasarkan Rata-rata nilai kepuasan penggunaan sistem informasi penjualan tanaman obat ada pada range 3.65 dengan kategori kepuasan adalah “BAIK” sehingga untuk pengunaan sistem informasi penjualan tanaman obat layak dan dapat digunakan dengan baik.Kata kunci:  Analisis , Penjualan Obat, PIECES Framework